THE EFFECTIVENESS OF INSTRUCTIONAL MEDIA TO THE USE OF JAPANESE YARIMORAI ON STUDENTS AT JAPAN LANGUAGE DEPARTMENT OF LANGUAGE AND ART FACULTY OF MANADO STATE UNIVERSITY - Jourike Jeane Runtuwarouw (Sekolah Tinggi Pariwisata Mataram, 2020)
This research is about how far instructional media affect the use of Japanese yarimorai acceptance expression. The goals of this research are (1) to find out students’ mastery level in using Japanese yarimorai acceptance expression, (2) to find out how far instructional media affect the use of Japanese yarimorai acceptance expression. Data of this research are from test result, and are processed statistically by using T-Test Formula with the help of qualitative and experimental research principles. Through quality assurance of data quality and interpretation process that is done carefully and actually, this research found some ideas which later will become ideas and study in effort of improvement of Japanese language education. The findings of the test results show that the average score of the group of students taught by using the image media is 8 with the standard deviation of 0.71 and the average score of the group taught without using the image media is 5.92 with standard deviation 0.64. The T test results reveal the significance of the mean difference is 6.5 with the experimental group learning outcomes higher than the control class. This proves that the use of media images have an effect on the use of Japanese acceptance expressions yarimorai